Epistemologi Islam - Nanang Tahqiq (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2003)
This paper will explore the foundations of Islamic teachings related to science, and provide contemporary examples of contributions by Muslim scientists. This brief introduction will discuss how Islamic epistemology maintains the essence of spirituality, an aspect often absent in Western epistemology. Islamic epistemology, as an integral part of Islamic teachings, offers a unique approach to knowledge that integrates both spiritual and rational dimensions. In this context, knowledge is not only seen as the result of logical and empirical processes but also as something connected to deep spiritual and moral understanding. Islamic teachings emphasize that knowledge should align with spiritual and ethical values, leading to a more holistic understanding of the world and human existence. The paper will also highlight the significant contributions of Muslim scientists in various fields, including mathematics, astronomy, medicine, philosophy, and social sciences. Contemporary examples from the works of Muslim scientists will demonstrate how the principles of Islamic epistemology are applied in their scientific practices. By examining the relationship between spirituality and knowledge in Islamic epistemology, this paper aims to offer insights into how this perspective can enrich our understanding of science and its contributions to modern society. It is hoped that this paper will provide a comprehensive overview of the relevance of Islamic epistemology and its impact on the development of knowledge and contemporary scientific thought.